The Influence of Indoor Air Condition on Microorganism Existing in Slum Area Around Pasupati Flyover and Cikapundung River. - Ningsih, Yulia; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
Tamansari is one of the dense urban villages in Bandung. Tamansari has an area of 102 ha with a population reached 24,897 inhabitants. Tamansari was passed by Pasupati bridge and Cikapundung river which led to high air pollution and water pollution. The dirty of environment and air are a good place for microorganisms to survive in the free air. It can cause various diseases. One of them is a disease in acute respiratory tract infections (ARI). Approximately 20% of children deaths under 5 years was caused by ARI. Streptococcus sp is one type of bacteria that cause respiratory disease. In this study used horse blood agar as a medium for Streptococcus sp growing. Results of this research conducted on 30 houses in RW 4, 10, 11 and 15 obtained the average of housing area and ventilation are 4.52 m2/person and 0.302 m2 for about 29 m2 floor area. The average value of wet temperature, dry temperature, humidity and air pressure are 22.23 0C; 26.95 0C; 66.83% and 0.92 atm respectively. The average density of total bacteria and Streptococcus sp were 1632 organism/m3 and 107 organism/m3. Ventilation is one of the factors influence the bacteria density in the air. Smaller ventilation cause greater bacteria density in the air. It is indicated by correlation coefficient about -0.146.Despite the number of bacteria density is not always equal for the same residential area, but there is a tendency that the bacteria density in the air increases with the narrowing of residential area per person. It is indicated by coefficient correlation between housing area/person with a bacterial density about -0.292.